Adaptive Management Decision-Making Tool in the Field of Regulation of Interaction of Subjects Participating in a Cluster of Regional Economic System - Barbara, Anna D.; Galstyan, Armen Sh.; Goloshchapova, Ludmila V.; Panchenko, Evgenia V.; Nikonova, Svetlana A.; Budeeva, Olga N. (International Review of Management and Marketing, 2016)
In this study, the authors identify the priority use of the cluster approach to the management of enterprises in the social and economic development of territories at the expense synergies from the combination of various enterprises and improve the quality and competitiveness of the manufacturing process. The study found that the clusters in regional economic systems of the Russian Federation are innovation-oriented production and the economy, based on cutting-edge world experience in science and technology that can create products with high added value is in demand, to provide the advantages of the opportunities that it gives the globalization of the world economy. However, the detection of the leading cluster and the planning of their formation and development, in particular in goal-setting in the cluster must be considered and the boundaries and parametric characteristics scale vector strategies regional economic system. Keywords: cluster, regional economy, management decisions JEL Classifications: G1, P25